1981
DOI: 10.1152/ajpcell.1981.240.1.c80
|View full text |Cite
|
Sign up to set email alerts
|

pH regulation in barnacle muscle fibers: dependence on extracellular sodium and bicarbonate

Abstract: Intracellular pH (pHi) regulation was studied in barnacle muscle fibers with pH-sensitive microelectrodes. The cells were acid loaded, and the subsequent recovery of pHi was monitored. The rate of recovery was reduced by one-third when external Na+ ([Na+]o) was replaced by Li+, but recovery was completely abolished when Na+ was replaced by choline or N-methyl-D-glucamine. In other experiments, varying amounts of Na+ were replaced by choline, and the acid extrusion rate, derived from the recovery rate of pHi, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
61
1

Year Published

1984
1984
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(67 citation statements)
references
References 10 publications
5
61
1
Order By: Relevance
“…The half-time for the decrease in at1 immediately after reintroduction of C02/HCO3 was 1-79±0-16 (n = 18, measured during the first 4 min). (Boron, McCormick & Roos, 1981;Moody, 1981). Consistent with this interpretation is the finding that the loss of Cl was more affected by the removal of CO2 from the superfusing solution than was the reaccumulation.…”
Section: Resultsmentioning
confidence: 56%
“…The half-time for the decrease in at1 immediately after reintroduction of C02/HCO3 was 1-79±0-16 (n = 18, measured during the first 4 min). (Boron, McCormick & Roos, 1981;Moody, 1981). Consistent with this interpretation is the finding that the loss of Cl was more affected by the removal of CO2 from the superfusing solution than was the reaccumulation.…”
Section: Resultsmentioning
confidence: 56%
“…In other experiments, SITS was less effective, and when we tried to make a solution containing both amiloride and SITS we obtained a precipitate. (Thomas, 1977;Boron, McCormick & Roos, 1981;Moody, 1981;Boron & Russell, 1983). When we initially tested the effects ofremoving Na on pH, recovery of leech neurones in a HC03--buffered solution, we found that some recovery still occurred.…”
Section: Leech Neurone Ph3mentioning
confidence: 99%
“…The best-characterized pHi regulatory mechanism in mammals is sodium/hydrogen (Na+/H+) exchange (1)(2)(3)(4)(5). In some cells pH, is also regulated by bicarbonate (HCO-) transport, including (a) Na+-dependent Cl-/HCO-exchange in invertebrate (6)(7)(8)(9) and also in mammalian cells (10)(11)(12)(13)(14), (b) Na+-independent This study was presented in part at the American Gastroenterological Association Meeting, New Orleans, May 1988. (1988.…”
Section: Introductionmentioning
confidence: 99%